HABITUS OPERATIVUS BONUS : Keutamaan Menurut St. Thomas Aquinas - Nadeak, Largus (UNIKA Santo Thomas, 2004)
St. Thomas Aquinas defines virtue as a good habit bearing on activity or a good faculty-habit (habitus operativus bonus). He adopts his idea from Aristoteles’ opinion. Aristoteles defines it as mean (mesotes) between two vices. Basic to the concept of virtue is the element of habit, which stands in a special relation to the soul, whether in the natural order or elevated to the divine life by grace (moral virtues and theological virtues). Back to virtue is a calling, so that people in our era is consistent in committing good acts.